Cardioprotective effects of colchicine: Targeting pyroptosis and inflammation in myocardial infarction - Satrijo, Budi; Mohammad Saifur Rohman; Aulanni'am Aulanni'am; Hidayat Sujuti; Bayu Lestari; Rislan Faiz Muhammad (Heart Science Journal, 2025)
Myocardial infarction (MI) is a significant contributor to global morbidity and mortality. The outcome of MI is associated with the inflammatory response triggered by ischemic or necrotic cells. Pyroptosis is a type of programmed cell death that can exacerbate cardiac injury following MI. This study reviewed the potential therapeutic effects of colchicine in regulating cardiac pyroptosis in response to MI. Primarily, colchicine inhibits tubulin polymerization and microtubule formation, disrupting inflammasome advancement and the subsequent secretion of various pro-inflammatory mediators. In particular, colchicine disrupts the NLRP3 inflammasome assembly process by blocking ASC recruitment into the complex, suggesting its potential to mitigate the inflammatory response related to cardiac pyroptosis. Additionally, colchicine binds to P2X7 receptors, reducing ATP-induced microtubule and pore formation, which attenuates reactive oxygen species and IL-1β production. A clinical trial involving colchicine showed positive outcomes in lowering the occurrence of major cardiovascular events in individuals with coronary artery disease (CAD). Nonetheless, additional studies are required to ascertain the ideal dosage, timing, and long-term effects of colchicine in the infarcted myocardium before it can be routinely recommended for post-MI treatment. In conclusion, colchicine's modulation of the inflammatory response and inhibition of pyroptosis highlight its potential as a cardioprotective agent for MI management.